STRENGTHENING THE STRATEGIC ROLE OF NEWBORN CARE CULTURE IN TENGGER TRIBE SOCIETY IN REDUCING INFANT MORTALITY RATE BASED ON TRANSCULTURAL NURSING - Puspitasari, R.A. Helda; Handayani, Dwining; Dewi Nastiti, Ayu; Kusuma, Erik; Rahmawati, Iis (Universitas Airlangga, 2026)
Introduction: The Tengger Tribe is an indigenous tribe in the Bromo Mountains, Pasuruan Regency. The community still strongly upholds customs and traditions in their daily lives, for example in caring for newborns, they have a unique way that has been passed down from their ancestors. The specific objective of this study is to obtain a picture of the meaning and significance of the health experience of the Tengger Tribe mountain community in caring for newborns by identifying the health characteristics of the Tengger Tribe community, identifying factors related to the behavior of handling health problems in newborns qualitatively. Method: The research design used is qualitative with an ethnographic approach. Result: Infant growth and development are influenced by environmental factors, these factors can be permanent or temporary, thus affecting the speed and quality of growth and development. Proper newborn care is intended for the child's physical growth including providing adequate and proper nutrition, protection against disease. The culture of newborn care in the Tengger tribe consists of exclusive breastfeeding, cutting the umbilical cord, baby massage, the role of midwives, the use of herbal plants as medicine for babies.. Conclusion: The behavior of cultural traditions in the Tengger community is generally good and very supportive of health. For further researchers, they can develop typical plants of the Bromo Tengger mountains that can be used for treatment when babies are sick. Keywords: culture; baby care; Tengger; infant mortality rate; transcultural.